ISOLASI DAN IDENTIFIKASI FUNGI PATOGEN DI KOLAM RENANG KOTA TANGERANG - Makhabbah Jamilatun Jamilatun; Aminah Aminah (Jurnal Ilmu dan Teknologi Kesehatan, 2017)
Swimming pool is a public facility that can be used as for recreation and exercise purposes. But the water quality is often left unknown. This research was aimed to isolate and identify the pathogenic fungi from the swimming pool in Tangerang City. It was a descriptive research with laboratory tests. The population in the study was the environment of Tangerang City swimming pool. Samples were taken by purposive sampling at several points of the pool, i.e. the pool water, tap water, shower room water, poolside, toilet wall and floor, and changing room. The results indicated that there was pathogenic fungi contamination in Tangerang City swimming pool. The pathogenic fungi were identified as mold and yeast, found in the swimming pool water: Aspergillus sp., Trichophyton sp.; shower room water: Penicillium sp., Mucor sp.; poolside: Penicillium sp.; toilet wall and floor:Mucor sp., Candida sp.; and changing room: Penicillium sp, Trichoderma sp, Candida sp. The presence of pathogenic fungi in this pool might be caused by contamination of fungal airborne spore, pool users, birds or cats droppings, as well as the temperature and humidity factors that support fungi growth.